(untitled) (Altre Modernità, 2018)
The use of corpus linguistics for technical translations has largely been advocated by scholars over the years. This paper is aimed at providing instances of legal term search in online parallel and comparable corpora. In particular, it will highlight that they can be used jointly in order to deliver accurate legal translations and dispel linguistic doubts. To this aim, Italian legal lexical phrases and formulaic expressions will be searched in the Italian section of the Bononia Legal Corpus (the BoLC). Then, the translation equivalents of the lexical phrases will be searched in the European Parliament Proceedings Parallel Corpus (the Europarl). Finally, the proposed equivalents will be queried in the English section of the BoLC, where they will be analysed, together with their collocations and concordance lines. The findings of this paper will highlight that online parallel and comparable corpora can be considered reliable legal translation tools, especially if used jointly.